Original synthetic monophenolic antioxidant with combined effect inhibits tumor growth in vivo - E. B. Menshchikova; M. V. Khrapova; P. M. Kozhin; A. V. Chechushkov; E. S. Petrova; A. E. Serykh; L. P. Romakh; N. V. Kandalintseva (Сибирский научный медицинский журнал, 2025)
Reactive oxygen metabolites and antioxidants, as well as the redox-sensitive signaling Nrf2-dependent pathway, play a dual role in the formation, growth and progression of malignant neoplasms. The aim of the study was to investigate the ability of the original synthetic monophenolic antioxidant of combined action to influence tumor growth in vivo and the side effects of cytostatic use. Material and methods. Lewis lung carcinoma (LLC) was used as an experimental model of malignant growth. The study was performed on 120 female C57Bl/6 mice, which were divided into 12 groups; the animals were weighed weekly. Mice of the corresponding groups received intragastrically a solution of sodium 3-(3′-tert-butyl-4′-hydroxyphenyl)propylthiosulfonate (TS-13) (100 mg/kg body weight), a suspension of tert-butylhydroquinone (tBHQ) or a solvent (0.9% NaCl solution) throughout the experiment. 28 days after the start of TS-13 and tBHQ administration, mice were implanted intramuscularly with a suspension of LLC cells at a dose of 2×105 cells/mouse; on the 7th and 14th days of tumor development, a solution of doxorubicin was administered intraperitoneally twice at a cumulative dose of 8 mg/kg body weight (4/5 LD10). On the 35th day of tumor growth, the animals were removed from the experiment, the tumor was extracted, weighed and its linear dimensions were determined; the tumor mass coefficient and volume were calculated, respectively. The spleen mass coefficient was also estimated. Results and discussion. On the 7th and 14th days of tumor growth, the body weight of animals receiving TS-13 and tBHQ was statistically significantly greater than that of other tumor carriers. Administration of TS-13 to mice inhibited tumor growth as effectively as doxorubicin, and more significantly when used in combination; tBHQ did not exert an independent inhibitory effect, and did not enhance its effect in combination with the cytostatic. Doxorubicin significantly reduced the spleen mass coefficient, while TS-13 and tBHQ statistically significantly reduced the effect of the cytostatic. Monotherapy with doxorubicin was accompanied by hair loss on the dorsal surface (8 animals out of 10), while no alopecia was observed with the combined administration of the cytostatic with TS-13 and tBHQ. Conclusions. Monophenol TS-13, a direct antioxidant and inducer of the Keap1/Nrf2/ARE system, is comparable to doxorubicin in terms of its antitumor effect. The use of TS-13 allows to significantly reduce the negative manifestations associated with malignant growth and the side effects of chemotherapy, such as cachexia, splenotoxity, and alopecia.